2019
DOI: 10.5194/tc-13-2457-2019
|View full text |Cite
|
Sign up to set email alerts
|

On the multi-fractal scaling properties of sea ice deformation

Abstract: Abstract. In this paper, we evaluate the neXtSIM sea ice model with respect to the observed scaling invariance properties of sea ice deformation in the spatial and temporal domains. Using an Arctic setup with realistic initial conditions, state-of-the-art atmospheric reanalysis forcing and geostrophic currents retrieved from satellite data, we show that the model is able to reproduce the observed properties of this scaling in both the spatial and temporal domains over a wide range of scales, as well as their m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
160
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 81 publications
(174 citation statements)
references
References 61 publications
14
160
0
Order By: Relevance
“…previous version of neXtSIM including an elasto-brittle (EB) rheology as described in Bouillon and Rampal (2015), showing good agreement with observed drift and concentration in particular. More recently, Rampal et al (2019) showed the ability to reproduce the characteristic multi-fractal scalings of deformation when using the current version of neXtSIM, which now includes the MEB rheology. Rampal et al (2019) update the paper of Rampal et al (2016), evaluating the model's improved performance when using the new MEB rheology.…”
Section: The Nextsim Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…previous version of neXtSIM including an elasto-brittle (EB) rheology as described in Bouillon and Rampal (2015), showing good agreement with observed drift and concentration in particular. More recently, Rampal et al (2019) showed the ability to reproduce the characteristic multi-fractal scalings of deformation when using the current version of neXtSIM, which now includes the MEB rheology. Rampal et al (2019) update the paper of Rampal et al (2016), evaluating the model's improved performance when using the new MEB rheology.…”
Section: The Nextsim Modelmentioning
confidence: 99%
“…More recently, Rampal et al (2019) showed the ability to reproduce the characteristic multi-fractal scalings of deformation when using the current version of neXtSIM, which now includes the MEB rheology. Rampal et al (2019) update the paper of Rampal et al (2016), evaluating the model's improved performance when using the new MEB rheology. The key addition of the MEB rheology is a viscous dissipation of stress in 5 areas where the ice is damaged, which restricts the velocity and particularly convergence in those areas.…”
Section: The Nextsim Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we compare the properties of lead fraction statistics calculated from passive microwave satellite data to that simulated by a continuum sea ice model. The model used, neXtSIM, is the first model that was shown to reproduce the observed multifractality of sea ice deformation rates in both space and time (Rampal et al, 2019). 60 Section 2.1 presents briefly the model setup, as well as the data and the methodology of the scaling analysis performed in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the probability distribution functions 50 (PDF) of open water densities, floe sizes, and deformation rates share the common property of a "heavy tail" (Rothrock and Thorndike, 1984;Matsushita, 1985; Stern et al, 2018;Weiss, 2003;Marsan et al, 2004;Marcq and Weiss, 2012) that is a sign of scale-invariance. Deformation rates Hutchings et al, 2011;Bouillon and Rampal, 2015a;Rampal et al, 2019) and open water densities (Weiss and Marsan, 2004) have been shown to display multifractality in the space domain and, in the case of deformation rates, in the time domain also (Weiss and Dansereau, 2017;Rampal et al, 2019). This 55 2 https://doi.…”
mentioning
confidence: 99%